The Cognitive-Vestibular Compensation Hypothesis: How Cognitive Impairments Might Be the Cost of Coping With Compensation - Lacroix, Emilie; Deggouj, Naïma; Edwards, Martin Gareth; Van Cutsem, Jeroen; Van Puyvelde, Martine; Pattyn, Nathalie (Frontiers in Human Neuroscience, 2021)
Previous research in vestibular cognition has clearly demonstrated a link between the vestibular system and several cognitive and emotional functions. However, the most coherent results supporting this link comes from rodent models and healthy human participant artificial stimulation models. Human research with vestibular-damaged patient studies show much more variability in the observed results, mostly because of the heterogeneity of vestibular loss, and the natural vestibular compensation process. The link between the physiological consequences of vestibular loss (such as postural difficulties), and specific cognitive or emotional dysfunction is not yet clear. Here, we suggest that a neuropsychological model, based on Kahneman’s Capacity Model of Attention, could contribute to the understanding of the vestibular compensation process and partially explain the variability of results observed in vestibular-damaged patients. Several findings in the literature support the idea of a limited quantity of cognitive resources that can be allocated to cognitive tasks during the compensation stages. This basic mechanism of attentional limitation may lead to different compensation profiles in patients, with or without cognitive dysfunction, depending on the compensation stage. We will suggest several objective and subjective measures to evaluate this cognitive-vestibular compensation hypothesis.